REKONSTRUKSI KURIKULUM PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM PASCAPEMERINTAHAN ORDE BARU - Said, Hamka (Hunafa: Jurnal Studia Islamika, 2009)
This research studies Islamic education curriculum reconstruction in High Public Education Institution after the fall of the New Orde. The main focus of this research is to investigate the form of the reconstruction and its relevance to the stakeholdersâ needs. The issue was studied by using qualitative analysis through library research. The result shows that the paradigm of Islamic education curriculum in 2002 was different from that in the New Orde era (prior to 2000. This affects the changing of teaching material radically where the change becomes more relevant to the stakeholdersâ needs than the previous curriculum.Kata Kunci:Â Â Â  rekonstruksi kurikulum, Pendidikan Agama Islam, Orde Baru, Orde Reformasi